Strategi inovatif bank Aceh Syariah: Integrasi fintech dalam mendorong pertumbuhan UMKM lokal di era digital - Iman, Dwiki Muhammad (Maliki Interdisciplinary Journal, 2025)
The digital era demands Islamic financial institutions to innovate to address challenges and capitalize on opportunities, particularly in supporting Micro, Small, and Medium Enterprises (MSMEs) as pillars of the economy. This study aims to analyze the innovative strategies implemented by Bank Aceh Syariah through the integration of financial technology (fintech) to encourage the growth of local MSMEs in Aceh. This study uses a qualitative approach with a case study method, where data is collected through in-depth interviews, observations, and a literature review of the bank’s strategic documents. The results of the study identify several key strategies, namely: (1) Development of a fast and easily accessible Islamic digital financing platform; (2) Strategic collaboration with Islamic fintech and local startups; (3) Implementation of digital financial education and literacy programs for MSMEs; and (4) Utilization of data analytics for more inclusive credit assessments. The analysis shows that this fintech integration has successfully increased access to capital, expanded market reach, and improved operational efficiency of MSMEs. The conclusion of this study is that fintech integration that aligns with Islamic principles and the local context creates an inclusive and sustainable financial ecosystem. This strategy not only encourages the growth of MSMEs but also strengthens regional economic resilience and Bank Aceh Syariah’s contribution to realizing real economic justice.